Regional validation of retracked sea levels from SARAL/Altika over the South China sea and adjacent seas - Abdullah, N. N. (Asian Research Publishing Network, 2017)
This paper focuses on assessing the quality of sea level anomaly (SLA) data from the new generation of Ka-band SARAL/AltiKa satellite altimetry over the continental shelf of the South China Sea. The region consists of peninsulas, shallow seas, and small islands that produce complicated altimetric waveform patterns. The improved-accuracy of SLAs data from the MLE4, Ice1 and Ice2 retrackers which are provided in the AVISO-Sensor Geophysical Data Records (SGDR) were optimized in this study. The quality of retracked SLAs is assessed by making comparison with tide gauge data from six stations. In general, the percentage of data availability of Ice-1 retracker is superior ( > 68%) to those of MLE- 4 and Ice-2 retrackers. The improvement of percentage (IMP) also shows that Ice-1 retracker improves the standard deviation > 12% better than those of Ice-2 retracker. Over complex areas of Lubang and Ko Taphao Noi, the temporal correlation of Ice-1 retracker is superior (r > 0.80) to those of MLE4 and Ice-2 retrackers (r < 0.84). The root mean square error (RMS) error of Ice-1 retracker is the smallest ( < 10 cm) when compared to the other two retrackers over both regions. On the other hand, over Vung Tau, Geting and Bintulu, Ice-2 and MLE-4 retrackers have better correlations (r > 5.8) and lower RMS error ( < 34 cm) than those of Ice-1 retracker. It can be concluded that the Ice-1 and Ice-2 retrackers were superior for the coastal region of Maritime Continent.